Walking with rhythmic auditory stimulation in chronic patients after stroke: A pilot randomized controlled trial. (24th June 2019) - Elsner, Bernhard; Schöler, Almut; Kon, Thomas; Mehrholz, Jan
Abstract: Objectives: There is a lack of studies that evaluate the effects of different gait training (GT) interventions for patients after stroke in an outpatient setting. The aim of the present trial therefore was to evaluate the effects of two different outpatient GT programmes after chronic stroke. Methods: We randomly allocated patients into two groups of either a 4‐week overground GT with rhythmic auditory stimulation (RAS, n = 6) of 30 min, three times a week over 4 weeks or an overground GT without RAS (GT, n = 6) with same duration and intensity. Primary outcomes were walking velocity and capacity; secondary outcomes were the Berg Balance Scale (BBS) and stride length before and after interventions and at 12 weeks follow‐up. Results: Twelve patients after stroke (nine females; mean [ SD ] age 67 [9] years; duration of illness 67 [69] months; all left‐sided strokes) were included. Patients improved their walking velocity from baseline until the end of GT (RAS: median difference 0.05 m/s [interquartile range, IQR 0.06] and GT: 0.12 m/s [0.29]) and walking capacity (RAS: median difference 14 m [IQR 14] and GT: 41 m [79]). However, RAS and GT did not differ significantly ( p = .30 and p = .30, respectively). Patients improved from baseline until the end of intervention in BBS (RAS: median difference 4 points [IQR 4] and GT: 1 point [3]) and stride length (RAS: median difference 6.3 cm [IQR 12.1] and GT: 5.5 cm [8.8]). However, BBS and stride length did not differ significantly between groups ( p = .08 and p = .58, respectively). Conclusion: Walking with rhythmic auditory stimulation in chronic patients after stroke does not provide a beneficial effect on walking when compared with walking without rhythmic auditory stimulation.